Self-assessment of the professional qualification’s level and conditions for performing the surgical stage of dental implantation by dentists in Ukraine - Tsuperiak, Сергій Степанович; Mochalov, Юрій Олександрович; Shupiatskyi, Ілля Михайлович; Molozhanov, Ігор Олексійович; Getsko, Юрій Юрійович; Mar’yan-Yovbak, Вікторія Юріївна; Petretska, Світлана Юріївна (Actual Dentistry, 2023)
Introduction. In modern stomatology of Ukraine, dental implantation is recognized as one of the priority options for orthopedic rehabilitation of patients with partial or complete adentity. This type of treatment has become relatively affordable, common throughout the country and with fairly predictable results. A number of conducted studies have shown a gradual increase in the population of our country for requests for dental prosthetics based on implants (especially in the pre-war period). At the same time, in view of the health care reform, the reduction and reorganization of a significant number of dental health care institutions , the rapid introduction of updated methods of dental implantation also requires the development of a diagnostic base (increasing the availability of cone-beam computed tomography) and the mastering by dentists of treatment methods related to implantation and preparation of the jaws for such a complex procedure. There are also periodic conversations about the introduction of standardization in dental implantology in Ukraine. The purpose of the study: to determine the professional qualifications of dentists and the conditions for performing the surgical stage of dental implantation in Ukraine on the basis of an independent and anonymous survey. Research materials and methods. To implement the research goal, a questionnaire was developed in the form of a Google form, the link to which was distributed among practicing dentists who practice dental implantation. The form was distributed by e-mail and using messenger programs. The mentioned electronic form contained questions about the respondent's age, length of work experience and experience as a dentist, period of work in dental implantology, performance of a number of surgical interventions in the oral cavity, use of osteoplastic materials and antibacterial agents. Results. During the survey, separate information was established regarding the self assessment by dentists of their own qualification level in terms of performing surgical interventions related to the preparation of jaws for dental implantation and performing the surgical stage of the procedure itself. Such data related to average age, length of work experience by specialty, and experience in performing dental implantation. At the same time, the data on the frequency of performing certain surgical procedures during the month, the level of mastery of the sinus lifting technique, osteoplasty of the jaws, preservation of the dental alveolus after tooth extraction, the use of osteoplastic materials in dental practice, platelet concentrates and preventive courses of antibacterial drugs were clarified. Conclusions. Dental implantation is a relatively new high-tech direction of the development of dentistry, the active development of such technologies affects the general progress of dental science and is an area of implementation of many innovations, which requires prompt and high-quality training of dentists.